FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Dara Maulidina (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2014)
The objective of this research is to provide emerical evidence about factors that influence on financial distress. The examines factors on this research are financial ratio from statements of income and balance sheet. The sample consist of 52 companies which had net income positive, 77 companies which had net income negative. The statistic method used to test on the research hypotesis is descriptive analysis method. This results show that current ratio, (current asset to current liabilities), return on equity (net income to equity), return on asset (net income to total assets), debt-equity ratio (total debt to total equity), and total assets turn over (sales to total assets) are a significant influence on financial distress.